Effectiveness and Safety of the Switch from Remicade® to CT-P13 in Patients with Inflammatory Bowel Disease. (12th April 2019) - Chaparro, M; Garre, A; Guerra Veloz, M F; Vázquez Morón, J M; De Castro, M L; Leo, E; Rodriguez, E; Carbajo, A Y; Riestra, S; Jiménez, I; Calvet, X; Bujanda, L; et al.
Abstract: Background and Aims: To evaluate the clinical outcomes in patients with IBD after switching from Remicade ® to CT-P13 in comparison with patients who maintain Remicade®. Methods: Patients under Remicade® who were in clinical remission with standard dosage at study entry were included. The 'switch cohort' [SC] comprised patients who made the switch from Remicade ® to CT-P13, and the 'non-switch' cohort [NC] patients remained under Remicade®. Results: A total of 476 patients were included: 199 [42%] in the SC and 277 [58%] in the NC. The median follow-up was 18 months in the SC and 23 months in the NC [ p < 0.01]. Twenty-four out of 277 patients relapsed in the NC; the incidence of relapse was 5% per patient-year. The cumulative incidence of relapse was 2% at 6 months and 10% at 24 months in this group. Thirty-eight out of 199 patients relapsed in the SC; the incidence rate of relapse was 14% per patient-year. The cumulative incidence of relapse was 5% at 6 months and 28% at 24 months. In the multivariate analysis, the switch to CT-P13 was associated with a higher risk of relapse (HR = 3.5, 95% confidence interval [CI] = 2–6). Thirteen percent of patients had adverse events in the NC, compared with 6% in the SC [ p < 0.05]. Conclusions: Switching from Remicade® to CT-P13 might be associated with a higher risk of clinical relapse, although this fact was not supported in our study by an increase in objective markers of inflammation. The nocebo effect might have influenced this result. Switching from Remicade® to CT-P13 was safe.